A Fixed Human Umbilical Vein Endothelial Cell Vaccine With 2 Tandem Repeats of Microbial HSP70 Peptide Epitope 407-426 As Adjuvant for Therapy of Hepatoma in Mice. Issue 7 (September 2015) - Xu, Maolei; Zhou, Ling; Zhang, Yanli; Xie, Zeping; Zhang, Jing; Guo, Lin; Wang, Chunhua; Yang, Xiaoping
Abstract : Various studies have indicated that vaccination with endothelial cells targeting tumor angiogenesis is an effective approach for inhibiting tumor growth and metastasis. However, our previous study about a viable human umbilical vein endothelial cell (HUVEC) vaccine demonstrated that the antitumor efficiency of the targeted therapy using HUVEC plus appropriate adjuvant is feasible but need further optimization. In this study, glutaraldehyde-fixed HUVEC, tested as another antigen form, was conjugated with 2 repeats of mycobacterial HSP70407-426 (M2 ) to prepare a novel HUVEC-M2 vaccine, which was expected to have an enhanced antitumor efficacy. HUVEC-M2 was administrated in mice by subcutaneous immunization in both prophylactic and therapeutic procedures. Compared with HUVEC alone, HUVEC-M2 induced a more significant inhibition on the growth of H22 hepatocellular carcinoma in mice and prolonged the survival of H22 hepatocellular carcinoma–bearing mice in both prophylactic and therapeutic procedures. Meanwhile, specific CTLs as well as antibodies against tumor endothelium correlated well with the inhibition effect were evoked by HUVEC-M2, which indicated that antiangiogenesis was mainly responsible for the antitumor effect. Moreover, the attenuated tumor-induced angiogenesis in intradermal tumor model and reduced vessel density of the intradermal tumor in mice further confirmed the antiangiogenesis effect elicited by HUVEC-M2 . All the data suggested that M2 could be used as a potent adjuvant to conjugate with glutaraldehyde-fixed HUVEC for preparing HUVEC vaccines and would have important clinical implications for adjuvant cancer therapy.